2006
DOI: 10.1038/sj.emboj.7601399
|View full text |Cite
|
Sign up to set email alerts
|

Correction of aberrant imprinting of IGF2 in human tumors by nuclear transfer-induced epigenetic reprogramming

Abstract: Loss of genomic imprinting of insulin-like growth factor II (IGF2) is a hallmark of many human neoplasms. We attempted to correct this aberrant epigenotype by transferring nuclei from human tumor cells that showed loss of IGF2 imprinting into enucleated mouse and human fibroblasts that had maintained normal IGF2 imprinting. After nuclear transfer, the abnormal biallelic expression of IGF2 in tumor nuclei transiently converted to normal monoallelic imprinted expression in the reconstructed diploid cells. In tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 47 publications
6
60
0
Order By: Relevance
“…To delineate how this long-range CTCF-promoter interaction is involved in suppressing the expression of maternal Igf2, we first examined DNA methylation by sodium bisulfite sequencing (6). As previously reported (10, 31), we found that the Igf2 promoters were normally unmethylated on both alleles (Fig.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…To delineate how this long-range CTCF-promoter interaction is involved in suppressing the expression of maternal Igf2, we first examined DNA methylation by sodium bisulfite sequencing (6). As previously reported (10, 31), we found that the Igf2 promoters were normally unmethylated on both alleles (Fig.…”
Section: Resultssupporting
confidence: 57%
“…It would be of great interest to investigate whether such interchromosomal associations of CTCF are also accompanied by the recruitment of PRC2 proteins. Loss of IGF2 imprinting is a hallmark of many human tumors (11,22,27); it is associated with the loss of activity of a non-CTCF transimprinting factor(s) (6) and, in some cases, with aberrant methylation of the ICR (36). It will be important to determine whether PRC2 serves as a putative imprinting factor that is either inactivated or mutated in tumors in which IGF2 imprinting has been lost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, our findings suggest that the relative difference in the prevalence of regulatory sequences in fractionated mouse sperm chromatin reflects their preferential location in distinct geographical 'territories' within the nucleus and in this case closer to the nuclear periphery. CTCF is closely involved in establishing gene imprints and in the demarcation of chromatin boundaries (Ohlsson et al 2001, Chen et al 2006, Phillips & Corces 2009). Therefore, the relatively high representation of its binding sites in peripherally located MNDS fractions suggests that CTCF may itself play a role in establishing these domains during sperm differentiation.…”
Section: Saida and Othersmentioning
confidence: 99%
“…According to Andrew Hoffman, a professor of endocrinology at Stanford University (Palo Alto, CA, USA), an important discovery was a link between the imprinting of IGF2 and colon cancer (Cui et al, 2003). This has also raised hopes of treating several cancers through epigenetic reprogramming to restore normal gene expression, which is the focus of Hoffman's research (Chen et al, 2006). "We have been using epigenetic reprogramming of human tumour cells to alter epigenetic marks, and have developed evidence that we can restore normal imprinting in tumour cells in which IGF2 imprinting has been lost," said Hoffman.…”
mentioning
confidence: 99%